A rare case of atypical bone marrow sarcoidosis without pulmonary involvement in a Japanese woman. Issue 6 (29th June 2021) - Iwata, Maki; Kodama, Tatsuya; Takeo, Hiroaki; Mataki, Norikazu
Abstract : Sarcoidosis is a systemic granulomatous disease of unknown origin characterised by the presence of non-caseating granulomatous lesions. Extrapulmonary sarcoidosis with bone marrow involvement is rare and even more so without pulmonary involvement. Here, we describe a case of 69-year-old woman diagnosed as having bone marrow and hepatic sarcoidosis without pulmonary involvement based on 18 F-fluorodeoxyglucose positron emission tomography findings. She was successfully treated with systemic glucocorticoid therapy.